Assessment of Environmental Hazards and Vulnerability of The Rud–E-Shur, Rud-E-Shirin and Rud-E-Minab International Wetland Using the DPSIR Model - Hengameh Safa Eisini; Saber Ghasemi; Afshin Danehkar; Mohsen Dehghani Ghanateghestani; Hossein Parvaresh (محیط زیست و توسعه فرابخشی)
Introduction: Mangrove forests in Iran are spread over about 11,000 ha and in the shores of the Persian Gulf and the Oman Sea, between 25º 11 to 27º 52´ from Goatar Bay in Sistan and Baluchistan province to Bardkhon in Bushehr province. These forests are valueable due to the having sensitive biophysical resources, breeding important and biodiversity. At the same time, they are in the rank of one of the most important marine sensitive areas and need proper management. The purpose of this study is to assess the risks of mangrove forests in the international wetlands of Rud-e-Shur, Rud-e-Shirin and Rud-e-Minab using the DPSIR model.Materials and Methods: Based on the studies of existing documents, as well as the opinions and experts, environmental hazards were identified in the investigation of Driving Forces, Pressures, State, Impacts and Responses models. Finally, using the Delphi phase, out of a total of 78 factors threatening of wetland, a total of 30 environmental risks were identified and prioritized. At the second stage, the intensity of the effect, the probability of occurrence and the sensitivity of the environment accepting the specified risks and threats are scored in five categories: very high, high, medium, low and very low (in the numerical range of 1 to 5) and finally using the method TOPSIS and TOPSIS Solver software were rated.Results: The results of the study showed that 30 risky factors including 24 human and 7 environmental origin cases; put living and existence of International Wetland into danger and risk. 5 threat indicators with human origin include population growth, human activities, excessive harvesting of ecosystem services, aquaculture, and management weakness; 2 threat indicators with environmental origin include drought and climate change have been prioritized. Based on the results of risk factors rankings, human and aquaculture activities were identified in particular order with 0.912 and 0.648 coefficient as two intolerance ranks among threat indicators factors in the international wetland. Also, oil smuggling, destruction of habitat, and transmission of shrimp farming effluent into Wetland, was classified as 1, 0.87, 0.75 respectively, ranking in the first to third risk factors.Discussion: According to the amount of Cli, two factors of oil smuggling and destruction of habitats are categorized in intolerable risks. Two factors of the transfer of wastewater from shrimp farms to the wetland and water pollution are categorized at the noteworthy category, as well as the countless traffic of vessels inside the lagoon and the creation of shrimp farm channels in the estuaries leading to the lagoon are in the category of tolerable risks, respectively, in the first to sixth priorities, which require control measures to reduce environmental risks. In order to protect the studied international wetland, it is necessary to promote public information about the ecological characteristics and effects of the wetland in the environment of the province, as well as the threats facing them through public education. Educating everyone about the necessity and method of protecting the environment of wetland and the effects of neglecting its destruction, drafting laws, regulations, criteria and executive standards regarding fuel smuggling, along with the appropriate executive guarantee of the government and finally the organization's forecast. Implementation guidelines and mechanisms to include environmental considerations in the country's development plans are the pillars without which the desired goals cannot be achieved.